A randomized trial to compare smooth monofilament suture vs. barbed suture using the three-layer continuous closure technique in canine ovariohysterectomy in a high-quality high-volume spay/neuter clinic - Shivley, Jacob M.; Brookshire, W. Cooper; Shealy, Alex P.; Seyer, Chase A.; Bushby, Philip A.; Woodruff, Kimberly A. (Frontiers in Veterinary Science, 2024)
The primary objective of this study was to compare time efficiency and complication rates between smooth monofilament suture (SMS) and barbed suture (BS) using the three-layer continuous incisional closure pattern after ovariohysterectomy in a high-quality high-volume spay neuter clinic. The study was designed as a randomized controlled trial enrolling 71 adult female dogs. Dogs were randomly assigned to SMS or BS treatments. The effect of closure with BS or SMS on closure time was tested by multilevel, multivariable linear regression in a generalized linear mixed model. Body condition score, weight, and pre-closure incision length were tested as covariates. Surgeon was included in the model as a random effect. Pre-closure incision length (p= 0.01) and method (p=<0.0001) were associated with closure time. Adjusting for pre-closure incision length, the average time for closure with SMS was 6.5 minutes (range 3.70-10.31 minutes), and the average time for closure with BS was 4.91 minutes (range 3.05-8.05 minutes). Accounting for closure method, the closure time increased by 39 seconds for each additional cm of incision length. Barbed suture was more efficient than SMS when performing the three-layer continuous suture pattern. No short-term telemedicine assessed complications were noted with either treatment method. Barbed suture can improve efficiency in surgical closures, especially considering large volumes of animals, and appears to have a similar short-term, telemedicine assessed complication rate when compared to SMS.